(untitled) (Research, Society and Development, 2020)
The academic environment provides new discoveries, social interactions, self-knowledge and countless other advantages. However, the students are exposed to high levels of stress and pressure constantly, which can lead to the development of mental disorders. Thus, the aim of this article is to describe the risk factors associated with the development of mental disorders in university students. A narrative bibliographic review was made using scientific articles from the last 20 years, through Medline, the Cochrane Library Database, Lilacs, PubMed, SciELO, Research Gate, Science Direct, PePSIC, Psicologado and FioCruz databases; the descriptors used were Mental health; Risk factors; Students; Mental disorders and the boolean AND. The difficulty encountered in the university transition is clear due to the high expectations followed by disenchantment for the institution or even for the chosen course. The overload of the proposed activities leads to physical and mental exhaustion of students, who choose to resort to certain drugs to maintain high academic performance. The relationship between some substances and the development of mental disorders was discussed, and symptoms of anxiety and depression gained prominence, associated or not with suicide. As a consequence of the extensive academic journey, there is the use of stimulants, the quality and sleep time are impaired, negatively influencing well-being and mental health. Therefore, the detection and treatment of mental disorders should be performed as soon as possible, with the purpose of sparing the detriment of the physical and psychic performance of future professionals in the country.